Evaluating Aztreonam and Ceftazidime Pharmacodynamics with Escherichia coli in Combination with Daptomycin, Linezolid, or Vancomycin in an In Vitro Pharmacodynamic Model - LaPlante, Kerry L. (American Society for Microbiology (ASM), 2009)
In an in vitro pharmacodynamic model, linezolid attenuated the activity of aztreonam and ceftazidime against Escherichia coli. Conversely, synergy was detected at 24 and 48 h when daptomycin or vancomycin was added to aztreonam and ceftazidime. We conclude that significant yet underappreciated interactions may occur between gram-positive-spectrum and gram-negative-spectrum antibacterials.